The use of diabetes mellitus exercise videos in health promotion media product testing - Febri Sri Lestari; Ridwan Setiawan; Iryanti Iryanti; Kusmiyati Kusmiyati; Asep Kuswandi; Faza Nurfadhilah; Atin Karjatin (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Diabetes Mellitus (DM) is a non-communicable disease with an increasing prevalence in Indonesia. Various management and prevention efforts, including DM exercise programs, have been implemented. To support independent exercise practice through audiovisual tutorials, appropriate exercise video media are needed. Objective: To examine the display quality and ease of following movements in DM exercise videos. Methods: This study employed a Sequential Exploratory Mixed Methods design. The qualitative phase involved five experts, consisting of one internal medicine specialist and Chair of the Indonesian Diabetes Association (PERSADIA), two exercise instructors, one sports health expert, and one media expert. The quantitative phase involved 10 participants in the PERSADIA Cimahi exercise. Data were collected through purposive sampling and guided interviews. Qualitative data were analysed using thematic analysis, while quantitative data were used to assess instrument validity, reliability, and video feasibility. Results: Thematic analysis identified two main themes: DM exercise material content and exercise video production aspects. The qualitative findings were used to develop a video assessment instrument. Instrument validation using Pearson product-moment correlation showed all items were valid (r > 0.361), while reliability testing yielded a Cronbach’s alpha of 0.919. The feasibility assessment produced a total score of 392 out of 450 (87.11%), indicating that the video was categorised as “very worthy”. Conclusion: DM exercise videos are considered very worthy for use.